HINDUTVA: WHIPPING UP SLEEPING SLAVES - V. T. Rajshekar (Journal of Dharma, 2004)
It is a fact that a micro-minority of about 3% Brahmanical forces had never failed even once in their attempt to defeat and enslave the non-Aryan natives ever since they divided, defeated, destroyed and finally drove Buddhism out of India about 2,500 years ago. By the end of the 10th century, Buddhism was practically stamped out of India.